Lean product development performance measurement tool - Al-Ashaab, Ahmed; Petritsch, Christoph; Gourdin, Mathilde; Urrutia, Usue Aliende; Andino, Alberto; Varro, Brigitta; Rigatti, Carlotta; Golob, Matic; Summers, Mark; El-Nounu, Abdulrahman (Cranfield University Press, 2013)
The need of applying lean thinking to product development is becoming a must for the organisations to success in the current industry. This paper presents a tool that helps to define the actual status of the organisations in relation to the lean principles. Extensive literature highlighted the need of developing a tool focused on assessing the implementation of lean principles themselves, rather than quantitate metrics. Based on the Balanced Scorecard, four perspectives, with corresponding set of questions, were defined reflecting the enablers of the product development model proposed by the LeanPPD European project. A five-level scale was customised to score the different readiness levels that define the transformation into a full lean implementation. The tool was used to assess the current and desired lean situation of an aerospace company within the research environment and resulted to be accurate to define the starting condition of the company to adopt leaner practices.
Keywords: LeanPPD; Lean Transformation; Lean Assessment